Ureteral Occlusion: Device Strategies, Approaches, and Results - Benjamin Treutler; Sahana Kumar; Christopher Shallal; Aryaman Gupta; Sanjana Kumar; Nicholas Zhang; Sean Healy; Jayaram Mandavilli; Nehali Gupta; Elizabeth A. Logsdon; Jordan Shuff; E. James Wright; et al. (Advances in Urology)
Genitourinary tract injuries can occur in the urinary tract or reproductive system as a result of trauma-related pelvic fractures, iatrogenic lacerations or ligations, and radiation therapy for reproductive or digestive malignancies. Although surgical reintervention is possible for large urinary tract injuries, a key component for healing smaller injuries is the ability to divert urine from the injury site to prevent urine-wound contact. This enables the injury to heal prior to reintervention and can eliminate the need for a secondary procedure, reducing the potential for complications. This type of urinary diversion is required by 140,000 patients in the United States annually, leading to the development of several devices to divert urine. The current standard of care includes minimally invasive procedures, such as placement of a catheter, double-J stent, or nephroureteral stent, but such measures often do not maintain sufficient dryness to enable wound healing. Based on a review of the literature, we have determined that successful devices need to prevent 100% of the anterograde urine flow, resist migration down the ureter because of peristalsis, and prevent urothelium growth over the device to promote wound healing without causing complications or necessitating reintervention. We also evaluated these devices according to the robustness of the study populations and designs in which they are reported. Some of the more successful devices include detachable, semicompliant balloons, platinum coils, and ureteral clips. Here, we present a narrative review of temporary and permanent ureteral occlusion devices and evaluate their potential for supporting wound healing. We also explore metrics by which to compare and select appropriate devices for urinary diversion.